STRATEGIC MANAGEMENT PRACTICE ON PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES : THE CASE OF GULLELE SUB CITY, ADDIS ABABA, ETHIOPIA - Alemu, Tegbew (Bina Nusantara University, 2025)
The aim of conducting this research was to determine the effect of strategy formulation, implementation and evaluation on the performance of small and medium enterprises. To carry out this study, the researcher have used a descriptive and explanatory research design to determine the relationship and effect of strategic management (strategy formulation, implementation, and evaluation) on performance. The study targeted 152 small and medium enterprises (SMEs) and from these 50 small and medium enterprises (SMEs) were determined as a sample but out of which 4 respondents did not return the questionnaire. Stratified probability sampling method was applied and data were collected from 46 SME managers through structured questionnaire using 5-point Likert scale. Primary data have been edited, classified, organized and coded to get descriptive and inferential statistics outputs using a professional software called Statistical Package for Social Science (SPSS) version 19. Regression analysis was done to determine the effect of strategy formulation, implementation and evaluation on performance, and correlation analysis was also conducted to determine the relationship between strategy formulation, implementation, evaluation and performance through inferential statistics. Finally, the finding shows that strategic management practice had a positive effect on performance. However, the only variable that affected performance was strategy implementation. Based on the findings, the researcher has recommended that all enterprises should have a written strategic intent, get training from strategic management consultants/ strategists, involve in training programs prepared by the authorities regarding enterprises and actively engaged in strategic management practice to increase their profit, output, market share, customer satisfaction and reduction of waste.